Examining the differential effects of information about the death penalty on retributivists and non-retributivists in Japan: a refutation of Marshall's third hypothesis - Watamura, Eiichiro; Ioku, Tomohiro; Mukai, Tomoya (Frontiers in Psychology, 2023)
This study aimed to test Marshall's third hypothesis-that information about the death penalty hardly affects the attitude of death penalty supporters on retribution grounds-utilizing a non-American sample. Four pre-registered experiments were conducted, involving Japanese participants randomly selected from sample pools of retributivists and non-retributivists, based on their reasons for supporting the death penalty. One group received information exposure, while the other was under control conditions. Participants read about deterrence (Study 1) or false convictions (Study 2-4). Except for the results of Study 4, retributivists and non-retributivists were equally affected or unaffected by information. Marshall's third hypothesis is therefore not supported. Retributivists strongly favored the death penalty; higher empathy toward criminals was associated with less prodeath penalty attitudes. Additionally, there were differences in the influence of information. These results suggest the need for a new approach to researching the relationship between public attitudes and information on the death penalty.